2022
DOI: 10.3390/cells11182886
|View full text |Cite
|
Sign up to set email alerts
|

A Charcot-Marie-Tooth-Causing Mutation in HSPB1 Decreases Cell Adaptation to Repeated Stress by Disrupting Autophagic Clearance of Misfolded Proteins

Abstract: Charcot-Marie-Tooth (CMT) disease is the most common inherited neurodegenerative disorder with selective degeneration of peripheral nerves. Despite advances in identifying CMT-causing genes, the underlying molecular mechanism, particularly of selective degeneration of peripheral neurons remains to be elucidated. Since peripheral neurons are sensitive to multiple stresses, we hypothesized that daily repeated stress might be an essential contributor to the selective degeneration of peripheral neurons induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In CMT, the MT-based transport is damaged by the enhanced binding of mutant heat shock protein beta-1 (HSPB1) to tubulin [ 184 ]. The increased binding of mutant HSPB1 to α-tubulin has been shown to inhibit AVs and protein aggregate transport along MTs [ 185 ]. In addition, HSPB1 mutants have been found to interact with p62 [ 186 ], which, in addition to its role in AV formation, has been found to promote AV motility and trafficking along MTs via a direct interaction with dynein [ 152 ].…”
Section: Compartmentalisation Of Neuronal Autophagymentioning
confidence: 99%
“…In CMT, the MT-based transport is damaged by the enhanced binding of mutant heat shock protein beta-1 (HSPB1) to tubulin [ 184 ]. The increased binding of mutant HSPB1 to α-tubulin has been shown to inhibit AVs and protein aggregate transport along MTs [ 185 ]. In addition, HSPB1 mutants have been found to interact with p62 [ 186 ], which, in addition to its role in AV formation, has been found to promote AV motility and trafficking along MTs via a direct interaction with dynein [ 152 ].…”
Section: Compartmentalisation Of Neuronal Autophagymentioning
confidence: 99%
“…In contrast, the S135F missense mutant of HSPB1 has a higher affinity for SQSTM1/p62 and HSPB1 facilitates the formation of SQSTM1/p62 bodies by binding to SQSTM1/p62, which is essential for the nucleation of phagophores that are capable of elongating to become mature autophagosomes [25]. During autophagy, autophagosomes transport from the cytoplasm to the perinuclear region along MTs, ultimately reaching perinuclear lysosomes for degradation [113]. HSPB1 was demonstrated to favor the formation of non-centrosomal MTs, but its binding to MTs appears to be weak and transient [114].…”
Section: Shsps Promote Autophagymentioning
confidence: 99%
“…HSPB1 was demonstrated to favor the formation of non-centrosomal MTs, but its binding to MTs appears to be weak and transient [114]. In contrast, the S135F missense mutant of HSPB1 has a higher affinity for SQSTM1/p62 and α-tubulin, which blocks the MT-dependent transportation of autophagosomes and has a negative effect on its function of promoting autophagy [25,113]. One study reported that sustained HSPB1 expression leads to ER stress, which subsequently activates the AMP-activated protein kinase 1 (AMPK1)/unc-51-like kinase 1 (ULK1) pathway [115].…”
Section: Shsps Promote Autophagymentioning
confidence: 99%
See 1 more Smart Citation